2015
DOI: 10.1002/j.0022-0337.2015.79.5.tb05913.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Adoption of Caries Management by Risk Assessment Among Dental Students in a University Clinic

Abstract: The aim of this study was to evaluate the long-term adoption of a risk-based caries management program at a university dental clinic. The authors extracted data from electronic records of adult non-edentulous patients who underwent a comprehensive oral evaluation in the university predoctoral clinic from July 2007 through June 2014 (N=21,984). Consistency with caries management guidelines was measured as the percentage of patients with caries risk designation (low, moderate, high, or extreme) and the percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Although the majority of predoctoral programs require their students to complete a caries risk assessment on all their patients and have a formal protocol for risk‐based preventative plans, not all students and faculty support implementation or adequate patient monitoring. These results are consistent with studies from other institutions . The results are even more disheartening within advanced prosthodontic programs, as only a third of programs required caries risk assessment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the majority of predoctoral programs require their students to complete a caries risk assessment on all their patients and have a formal protocol for risk‐based preventative plans, not all students and faculty support implementation or adequate patient monitoring. These results are consistent with studies from other institutions . The results are even more disheartening within advanced prosthodontic programs, as only a third of programs required caries risk assessment.…”
Section: Discussionsupporting
confidence: 89%
“…Scientific advancement has expanded the scope of preventive strategies, and several schools have modified their didactic and clinical curriculum relative to caries prevention and management education . Yet discontinuity exists between what is taught didactically, what is expected clinically, and what occurs operationally within dental schools.…”
Section: Discussionmentioning
confidence: 99%
“…Bringing this prevention‐based approach into dental clinical practice is not new; it has a long history in the dental education community 21,22 . However, “while efforts by dental educators may be essential, they may by themselves be insufficient to achieve the desired results”; 21 changes on the level of oral health care polices and organization, reimbursement systems, dental associations fees guide policies, dental national board exams, accreditation and licensure processes, insurance coverage, and public awareness levels are also essential.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidences showed that the successful implementation of risk-based caries management in clinical training should be improved through the calibration with a specific set of guidelines and assessing the accuracy of caries risk evaluation for both faculty members and students [2224, 51]. Future studies are needed to provide the training and calibration of other faculty members.…”
Section: Discussionmentioning
confidence: 99%